Development of the Test-System for Differentiation of Brucella Species, Using Real-Time PCR - Zh. A. Kas’yan; N. A. Osina; S. A. Shcherbakova (Проблемы особо опасных инфекций, 2016)
Objective of the study is to construct a test-system allowing for specific identification of brucellosis agent, using real-time polymerase chain reaction.Materials and methods. Carried out has been analysis of literature sources and nucleotide sequences of Brucella spp., applying the specialized software for DNA-target sequence selection, specific for each brucella species. Developed is methodological tool and reagent panel for identification of brucellosis agent species appurtenance by means of RT PCR using thermocycler with hybridization-fluorescent registration of results, RotorGene type.Results and conclusions. Developed is the test-system, providing for differentiation of brucella species or group of species: B. abortus/B. ovis; B. melitensis; B. suis/B. canis; B. neotomae, applying real-time polymerase chain reaction. BR0262, BRA0541-0542, BMEII0711 genes are selected as DNA-targets, being completely or partially deleted in different species of brucella.